SUSTAINABLE MARKETING: BALANCING PROFIT AND PLANET IN MODERN BUSINESS PRACTICES - Bunga Aditi; Eko Tama Putra Saratian; Marwan Effendi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research explores the impact of sustainable marketing strategies on corporate image and business profitability at The Body Shop Pekanbaru. Using a quantitative research design, this study used random sampling techniques to collect data from 250 consumers. The analysis used was structural equation modeling using SmartPLS to evaluate the relationship between variables. The findings indicate a significant positive correlation between the implementation of sustainable marketing strategies and corporate image, which in turn affects business profitability. However, the results show that customer satisfaction does not have a significant direct impact on profitability when mediated through sustainable marketing strategies. These insights suggest that while improving a company's image through sustainability efforts is critical to financial success, customer satisfaction alone cannot guarantee profitability without strategic integration with sustainability initiatives. This study highlights the importance of ethical branding and responsible practices in the beauty industry, offering implications for brands looking to align themselves with modern consumer values.